Cinema Queerité: gêneros e identidades minoritárias no documentário Paris is Burning - CORRÊA, Ademir Silveira (2017)
Paris is Burning (1990), a documentary by Jennie Livingston, when filming the ballroom circuit of the Harlem’s neighborhood in New York at the end of the 1980s, is built on its encounters with cinéma vérité and the new queer cinema movements, documenting minority identities as a practical proposal for the definitions of the Queer Theory for life. The purpose of this research is to develop a critical reflection to analyze this film, to recognize in its the urgency of the LGBTQIA themes for identities, desires and practices as narrative representations and the gender construction of gays, transgender women and black and Latino drag queens as answers to the plurality of human experience. The methodology used is anchored in the practice of film analysis and the reconstitution of scenes, performances and dialogues through reflections that include documentary film, mass culture and Queer Theory point to the documentary record of characters representative of minority identities that are also positioned in their differences, in order to perpetuate a survival struggle that is affirmed in the creation of queer ballroom culture.